2012
DOI: 10.1186/cc11675
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral care with versus without toothbrushing on the prevention of ventilator-associated pneumonia: a systematic review and meta-analysis of randomized controlled trials

Abstract: IntroductionVentilator-associated pneumonia (VAP) remains a common hazardous complication in mechanically ventilated patients and is associated with increased morbidity and mortality. We undertook a systematic review and meta-analysis of randomized controlled trials to assess the effect of toothbrushing as a component of oral care on the prevention of VAP in adult critically ill patients.MethodsA systematic literature search of PubMed and Embase (up to April 2012) was conducted. Eligible studies were randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 27 publications
1
33
0
8
Order By: Relevance
“…Both previous SR evaluating the OHM with versus without toothbrushing on the prevention of VAP concluded that toothbrushing does not promote a significant reduction in VAP incidence in mechanically ventilated patients. The first included only four studies and the second six, while the present SR included 12.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Both previous SR evaluating the OHM with versus without toothbrushing on the prevention of VAP concluded that toothbrushing does not promote a significant reduction in VAP incidence in mechanically ventilated patients. The first included only four studies and the second six, while the present SR included 12.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, a recent ‘overview of SRs’ by Rabelo et al found that the use of CHX was effective in preventing VAP in cardiothoracic intensive care unit (ICU). Another couple of SRs of randomized clinical trials (RCT) evaluating toothbrushing on the prevention of VAP did not find differences between OHM with toothbrushing versus without toothbrushing . However, and regardless of their significant work these SRs were published >5 years ago, and since then the base of evidence has improved.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] In most ICUs worldwide, oral care is performed by nurse staff, but they do not have enough training or legal permission to treat caries, remove calculus, drain intraoral abscesses, or perform tooth extractions, as critical patients may need. [25][26][27] In Brazil, many of these procedures are frequently needed because of the poor oral health of the general population, with a mean decayed/missing/filled/teeth index of 27.53 in the age range of 65-74 years. 28 Our data support the hypothesis that a dental surgeon may make a difference in this scenario, thus enhancing the effect of oral antiseptics and preventing around 56.0% of LRTI episodes.…”
Section: Discussionmentioning
confidence: 99%
“…In 2 Metaanalysen von 4 bzw. 6 Studien konnte kein Vorteil der mechanischen Zahnreinigung gefunden werden, allerdings ist die Evidenz aufgrund der kleinen Patientenzahl und einer hohen Heterogenität der Studien noch gering [148,149].…”
Section: Hygienische Mundpflegeunclassified